Anti-TWEAK Antibody Alleviates Renal Interstitial Fibrosis by Increasing PGC-1α Expression in Lupus Nephritis - Xue L; Zhang Y; Xu J; Lu W; Wang Q; Fu J; Liu Z (Dove Medical Press, 2021)
Leixi Xue,1,* Yi Zhang,1,* Jiajun Xu,1 Wentian Lu,1 Qing Wang,1 Jinxiang Fu,2 Zhichun Liu1 1Department of Rheumatology and Immunology, The Second Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China; 2Department of Hematology, The Second Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhichun LiuDepartment of Rheumatology and Immunology, The Second Affiliated Hospital of Soochow University, Sanxiang Road No. 1055, Suzhou, Jiangsu, 215004, People’s Republic of ChinaTel +86 13771994276Email liuzhichun5190@163.comJinxiang FuDepartment of Hematology, The Second Affiliated Hospital of Soochow University, Sanxiang Road No. 1055, Suzhou, Jiangsu, 215004, People’s Republic of ChinaTel +86 13962525217Email fjx3000@126.comPurpose: Current studies on the mechanism of tumor necrosis factor-like weak inducer of apoptosis (TWEAK) in lupus nephritis (LN) mainly focus on the inflammatory pathway. Herein, we aimed to determine whether TWEAK could promote the progression of renal interstitial fibrosis by regulating peroxisome proliferator-activated receptor-gamma coactivator-1α (PGC-1α) expression and intervening in lipid metabolism in LN.Materials and Methods: MRL/lpr mice, an animal model of lupus, were treated with the anti-TWEAK antibody or co-treated with adeno-associated virus-mediated PGC-1α short hairpin RNA (shRNA). In addition, human proximal tubular epithelial cells (HK2 cells) were treated with recombinant human TWEAK (rhTWEAK) or ammonium pyrrolidine dithiocarbamate (PDTC) in vitro.Results: The renal contents of free fatty acids and triglycerides were higher in MRL/lpr mice than in MRL/MpJ mice; however, these contents were decreased by treatment with the anti-TWEAK antibody. Based on immunofluorescence staining, the expression of PGC-1α was markedly more in the renal tubules of MRL/MpJ mice than in the glomeruli. However, treatment with anti-TWEAK antibody increased the levels of PGC-1α and its downstream target genes, which were remarkably lower in MRL/lpr mice than in MRL/MpJ mice. Anti-TWEAK antibody effectively eased renal interstitial fibrosis, which manifested as a decrease in the deposition of collagen fibers and the inhibition of type I collagen and fibronectin expression. However, the therapeutic effects of the anti-TWEAK antibody were abolished by PGC-1α shRNA. Treatment with rhTWEAK decreased PGC-1α expression in both dose- and time-dependent manners in HK2 cells in vitro. PDTC, an inhibitor of IκBα phosphorylation, suppressed the decrease in the PGC-1α protein level induced by rhTWEAK treatment.Conclusion: Our results suggest that TWEAK prevents renal tubular PGC-1α expression by promoting NF-κB activation, resulting in a deficiency in lipid metabolism and the progress of renal interstitial fibrosis. The upregulation of renal tubular PGC-1α expression to improve lipid metabolism is one of the mechanisms employed by the anti-TWEAK antibody to treat renal interstitial fibrosis.Keywords: TWEAK, lupus nephritis, renal interstitial fibrosis, PGC-1α, lipid metabolism